Experimental and numerical exploration of a new application of coal slag to treat loose sand foundation - Liu, Kaiwen; Qiu, Ruizhe; Gou, Jie; Ning, Bo; Cui, Chunyi; Chen, Yang; Wang, Tengfei (Journal of cleaner production, 2024)
The sustainable management of coal slag, a prevalent solid waste byproduct resulting from coal combustion, remains an enduring and paramount subject of investigation. This paper presents an approach of exploring the viability of coal slag as a sustainable substitute for conventional gravel in geosynthetic-encased columns by large-scale model tests and numerical simulation, with a focus on its potential to enhance loose sand foundation performance. The properties of coal slag were characterized through X-ray fluorescence (XRF), X-ray diffractometry (XRD), and leaching tests. The bearing and deformation characteristics of a 250-mm diameter geosynthetic encased coal slag column (GECSC) installed in loose sand foundation were compared with those of an untreated foundation by large scale physical model tests. The parametric study involving the stiffness and encased length of geosynthetic encasement, as well as the relative density of surrounding sand was performed based on the three-dimensional finite element model verified by experimental tests. The results show that the coal slag tested is an environmentally friendly material with huge potential as an alternative to gravel for encased columns in foundation treatment. Increasing the encasement stiffness enhances bearing capacity and reduces circumferential deformation. The GECSC technology is particularly well-suited for loose sand, exhibiting a noteworthy improvement ratio of 2.73 in sand with a relative density of 10 %. The cost-effective encasement length (i.e., double times of diameter) for partially encased GECSC is recommended in terms of controlling the maximum bulge. •Propose a new application of coal slag disposal with a sustainable alternative to the traditional granular column.•Perform XRD, XRF and leaching tests of coal slag adopted.•Conduct a large-scale model test for geosynthetics-encased coal slag column in loose sand.•Demonstrate the significant improvement of foundation treated by the proposed encased coal slag column.•Investigate key influential factors for the application of encased coal slag column in loose sand.